Prevalence, Associated Factors and Consequences of Unwanted Pregnancy in Iran - Mohammad Esmaeil MOTLAGH; Seiyed Davoud NASROLLAHPOUR SHIRVANI; Zahra HASSANZADEH-ROSTAMI; Farahnaz TORKESTANI; Seyed-Mozaffar RABIEE; Hassan ASHRAFIAN AMIRI; Laleh RADPOOYAN (Tehran University of Medical Sciences, 2020)
Background: Unwanted pregnancy is a type of unplanned pregnancy that can endanger health of mother and child. This study aimed to determine the prevalence of unwanted pregnancy and its associated factors and consequences in Iran. Methods: This cross-sectional study was conducted in regions with low, moderate and high risk of maternal death. Two provinces were randomly selected in each region and 24 public health centers in each province during 2007-2012. Thereafter, 15-20 mothers, received at least one session of pregnancy care, were selected from each healthcare center. Data were gathered from both health records and interview with the mothers. Results: Of 2714 participants, 86.4% and 13.6% had respectively wanted and unwanted pregnancies. The underlying factors of unwanted pregnancy were determined as low distance with previous and next pregnancy, economic problems and have enough children. Moreover, there were significant relationships between unwanted pregnancy and place of residence, mother's age and education, father's education, pre-pregnancy care and number of previous pregnancies and children. There were also significant association between unwanted pregnancy and pregnancy care, anemia, exposure to risk factors and disease, intake of folic acid and iron, domestic violence, bitter memories and men's participation. Conclusion: Although the prevalence of unwanted pregnancy has had a significant decrease in Iran, these mothers still require a higher level of educational, counseling and supportive services due to their low access to pregnancy care services and high exposure to associated risk factors.